Determinan Service Quality Terhadap Customer Satisfaction - Ramadhan Harahap (CERED Indonesia Institute, 2021)
This study aims to analyze the determination of the influence of services from Reliability, Responsiveness, Assurance, Empathy and Tangibles simultaneously affect customer satisfaction PT SVMG - Medan. This type of research is descriptive quantitative research, namely research that aims to describe or describe the properties (characteristics) of a situation or object of research, which is carried out through the collection and analysis of quantitative data and statistical testing. The test equipment in this study uses multiple linear regression models using t test and F test. The results of the F test prove that the variables of reliability (X1), responsiveness (X2), assurance (X3), empathy (X4) and tangibless (X5) simultaneously have a significant effect on Y (Customer Satisfaction ). The results of the t test prove that only responsiveness (X2), empathy (X4) and tangibles (X5) variables have a significant effect on customer satisfaction.